The Effects of Alpha Interferon on the Development of Autoimmune Thyroiditis in the NOD H2h4 Mouse - Yael Oppenheim; Grace Kim; Yoshiyuki Ban; Pamela Unger; Erlinda Concepcion; Takao Ando; Yaron Tomer (Clinical and Developmental Immunology)
Alpha interferon (αIFN) therapy is known to induce thyroid autoimmunity in up to 40% of patients. The mechanism is unknown, but Th1 switching has been hypothesized. The aim of our study was to examine whether αIFN accelerated the development of thyroiditis in genetically susceptible mice. We took advantage of NOD-H2h4, a genetically susceptible animal model, which develops thyroiditis when fed a high iodine diet. Six to eight week old male NOD H2h4 mice were injected with mouse αIFN (200 units) or with saline three times a week for 8 weeks. All mice drank iodinated water (0.15%). Mice were sacrificed after 8 weeks of injection. Their thyroids were examined for histology and blood was tested for antithyroglobulin antibody levels. T4 and glucose levels were also assessed. In the IFN-injected group, 6/13 (46.2%) developed thyroiditis and/or thyroid antibodies while in the saline-injected group, only 4/13 (30.8%) developed thyroiditis and/or thyroid antibodies (p=0.4). The grade of thyroiditis was not different amongst the two groups. None of the mice developed clinical thyroiditis or diabetes mellitus. Our results showed that αIFN treatment did not accelerate thyroiditis in this mouse model. This may imply that αIFN induces thyroiditis in a non-genetically dependent manner, and this would not be detected in a genetically susceptible mouse model if the effect were small. Alternatively, it is possible that αIFN did not induce thyroiditis in mice because, unlike in humans, in mice αIFN does not induce Th1 switching.